Bioactive Formulations in Agri-Food-Pharma: Source and Applications, Volume II - Sharma, Minaxi; Sridhar, Kandi; Usmani, Zeba (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint provides the most relevant and state-of-the-art in the field, including recent developments in the production of natural compounds from various bioresources, and their formulations as bioactives. This reprint also covered the engineered approaches for enhanced biological properties and their potential applications. Identification of novel compounds and bioprocess tools to improve the quantity and quality of bioactive compounds and their formulations are exclusively covered in this reprint.